Identifikasi Tingkat Ploidi Tanaman Pisang Menggunakan Flow Cytometer di Jawa Tengah - Herlina; Yuyu Suryasari Poerba; Tri Handayani; Fajarudin Ahmad; Diyah Martanti (LPPM Universitas Terbuka, 2024)
In Indonesia, banana plants are known to have high genetic diversity, both cultivated and wild bananas. Banana plants are naturally known to have several levels of ploidy, namely diploid, triploid, and tetraploid. This study aims to identify the level of ploidy in banana plants explored in Central Java. The research method used flow cytometer, which analyzes the size of the plant genome, thus providing an overview of the level of ploidy and genetic diversity in banana plant populations. The research samples were banana plant leaves from various exploration locations in Central Java. The identification results show that of the 30 banana plant leaf samples that were successfully analyzed, it is known that the largest number of samples from banana plants that have triploid ploidy level (2n = 3x), namely 15 numbers, diploid ploidy level (2n = 2x) as many as 14 numbers, and found 1 cultivated banana with tetraploid ploidy level (2n = 4x). The results of ploidy level identification can provide guidance for researchers and plant breeders in selecting the right genotype for the development of superior varieties.